Trajectories of Postload Plasma Glucose in the Development of Type 2 Diabetes in Japanese Adults. (14th September 2017) - Oka, Rie; Shibata, Kyoko; Sakurai, Masaru; Kometani, Mitsuhiro; Yamagishi, Masakazu; Yoshimura, Kenichi; Yoneda, Takashi
Abstract : We aimed to clarify how the trajectories of 1-hour postload plasma glucose (PG) and 2-hour PG were different in the development of type 2 diabetes. Using data of repeated health checkups in Japanese workers from April 2006 to March 2016, longitudinal changes of fasting, 1-hour, and 2-hour PG on the oral glucose tolerance test were analyzed with a linear mixed effects model. Of the 1464 nondiabetic subjects at baseline, 112 subjects progressed to type 2 diabetes during the observation period (progressors). In progressors, 1-hour PG and 2-hour PG showed gradual increases with slopes of 1.33 ± 0.2 and 0.58 ± 0.2 mg/dL/year, respectively, followed by a steep increase by which they attained diabetes. Until immediately before the diabetes transition, age- and sex-adjusted mean level of 2-hour PG was 149 ± 2.7 mg/dL, 34 ± 2.7 (30%) higher compared to nonprogressors, while that of 1-hour PG was 206 ± 4.1 mg/dL, 60 ± 4.3 mg/dL (41%) higher compared to nonprogressors. In conclusion, diabetes transition was preceded by a mild elevation of 2-hour PG for several years or more. The elevation in 1-hour PG was larger than that of 2-hour PG until immediately before the transition to diabetes.